Kerinduan pada Tanah Air dalam Antologi Puisi â€˜Ä€syiq Min Falisá¹Ä«n Karya Mahmoud Darwish (Analisis Semiotika Riffaterre) - Suharsono Suharsono; Ivan Adilla; Syofyan Hadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Anthology of poetry Mahmoud Darwish's work Ä€syiq min Falisá¹Ä«n is a poem about longing, which shows the poet's love for his homeland. On the other hand, the poetry in the anthology also describes the condition of the poet who is in prison, isolated and without a family. To discuss the poetry anthology above, this thesis utilizes the semiotic theory developed by Michael Riffaterre. There are three problems studied in this thesis, they are: 1) What is the form of indirect expression in the poetry anthology of Ä€syiq min Falisá¹Ä«n by Mahmoud Darwish, 2) What is the meaning contained in the anthology of poetry Ä€syiq min Falisá¹Ä«n Mahmoud Darwish's work with heuristic and hermeneutic readings, 3) How are the matrices, models, and variants in the poetry anthology of Ä€syiq min Falisá¹Ä«n by Mahmoud Darwish. The method used in this study is a qualitative descriptive that describes the results of research using Riffaterre's semiotics method. This research concludes the following. First, the indirect form of expression in the poetry anthology Mahmoud Darwish's work Ä€syiq min Falisá¹Ä«n is in the form of changing meaning, distorting meaning, and creating meaning. Second, through heuristic and hermeneutic reading, it can be concluded that the poems in the anthology above describe the poet's longing for his land of Palestine. Third, the matrix, model, and variant in the poetry anthology Mahmoud Darwish's work Ä€syiq min Falisá¹Ä«n shows the relationship between the themes of each stanza of his poetry.